Positive expiratory pressure (PEP) therapy. What pressures do we achieve in young children with cystic fibrosis? A single-centre study - Peter Anderson; Niamh Kiernan; Barry Johnstone; Ruth Stewart (BMJ Paediatrics Open)
This study was a clinical review of infant positive expiratory pressure (PEP) therapy in young children with cystic fibrosis (CF). The aim of this study was to determine whether pressures of 10–20 cm H2O PEP therapy (recommended by the CF trust) are being achieved with routine airway clearance therapy. This took place at the Royal Hospital for Children, Glasgow a specialist UK CF centre. Values were obtained from 21 young children. Pressures above 10 cm H2O during tidal volume breathing were not achieved within our cohort. Further investigation is required to determine efficacy of lower pressures in PEP therapy with young children.